2017
DOI: 10.1186/s12939-017-0654-3
|View full text |Cite
|
Sign up to set email alerts
|

Who pays for healthcare in Bangladesh? An analysis of progressivity in health systems financing

Abstract: BackgroundThe relationship between payments towards healthcare and ability to pay is a measure of financial fairness. Analysis of progressivity is important from an equity perspective as well as for macroeconomic and political analysis of healthcare systems. Bangladesh health systems financing is characterized by high out-of-pocket payments (63.3%), which is increasing. Hence, we aimed to see who pays what part of this high out-of-pocket expenditure. To our knowledge, this was the first progressivity analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…Our findings also indicated negative coefficients of the KPIs for the OOP payment for healthcare across the years and the categories, indicating the regressivity of the households’ OOP payments for healthcare services. These findings are consistent with the reports of other several studies [ 6 , 16 – 18 , 27 ]. Another study in Africa also reported a negative coefficient (KPI = − 0.20) of the OOP for healthcare [ 28 ].…”
Section: Discussionsupporting
confidence: 94%
“…Our findings also indicated negative coefficients of the KPIs for the OOP payment for healthcare across the years and the categories, indicating the regressivity of the households’ OOP payments for healthcare services. These findings are consistent with the reports of other several studies [ 6 , 16 – 18 , 27 ]. Another study in Africa also reported a negative coefficient (KPI = − 0.20) of the OOP for healthcare [ 28 ].…”
Section: Discussionsupporting
confidence: 94%
“…This is the case especially in the upper middle-income country such as Turkey (Yardim, Cilingiroglu, & Yardim, 2013), Iran (Rezapour et al, 2015) and China (Chen, Zhao, & Si, 2014) and some lower middle-income countries such as the Philippines (O'donnell et al, 2008), where OOP payments are paid according to population's ATP. However, some lower middle-income countries with big populations such as India (Chowdhury, Gupta, Trivedi, & Prinja, 2018) and Bangladesh (Molla & Chi, 2017), have a regressive OOP payments where the lower income populations, particularly in rural areas spent high proportion of OOP payments due to lack of access to public health care and lack of health protection scheme for the poor (Mondal, 2013), thus exposing the poorer population to risk of financial catastrophe and poverty.…”
Section: Progressivity Of Out-of-pocket Payments For Health Care: Intmentioning
confidence: 99%
“…Cost is one of the key barriers to adopting new interventions in the existing programs in low- and middle-income countries, and cost parameters are often estimated through recall [ 26 - 28 ]. The proposed research will capture the direct cost of the intervention based on actual activities involving the intervention in real time and estimate all possible realistic costs that would be incurred by both the schools (provider cost) and the participating families (out of pocket cost) due to integrating the proposed combined intervention.…”
Section: Introductionmentioning
confidence: 99%